Bogolyubov theorem for quasidifferential equations with pulses - Kitanov, P. M.; Plotnikov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider the averaging method for pulse quasidifferential equations in metric spaces.